Development of a Patient Safety Incident Reporting System using the Agile Development Method - Anam, Muhammad Khoirul; Astuti, Yani Parti; Mubarok, Ahmad Hasan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
One of the critical aspects of healthcare services is patient safety. However, the reporting of patient safety incidents in Indonesia remains low due to the use of inefficient manual systems and the limited participation of healthcare professionals. This study aims to develop a web-based patient safety incident reporting system using the Agile Development method. Agile was chosen for its ability to progressively adapt to user needs through fixed-duration iterations (sprints). The uniqueness of the system lies in the integration of the Agile approach with the Laravel architecture, which enables rapid, modular, and participatory development. Data were collected through interviews, questionnaires, and literature reviews, and analyzed using the PIECES framework. The system was developed using the Laravel framework and evaluated through User Acceptance Testing (UAT) with 24 respondents from the Temanggung District General Hospital (RSUD Kabupaten Temanggung). The testing results showed that 91% of respondents strongly agreed on the system's ease of use and effectiveness. The system has proven to enhance efficiency, accuracy, and user engagement in the incident reporting process. It also offers practical implications for other hospitals aiming to build more integrated and adaptive reporting systems to support improved healthcare service quality.